A systematic scoping review of adolescent mental health treatment using mobile apps. (3rd July 2019) - Gindidis, Simone; Stewart, Sandy; Roodenburg, John
ABSTRACT: Objective: Mobile apps provide opportunities for innovative, accessible and attractive support of adolescent mental health. Although preliminary research evaluates the effectiveness of specific apps for various conditions, the way in which apps are being used to support adolescent mental health and the role of particular app functions are not well understood. This study presents a systematic scoping review exploring app functionality and delivery method used in treating adolescent mental health concerns. Method: A systematic search of health sciences databases including Medline, PubMed and PsycInfo was undertaken in March, 2017. Seven studies were identified totalling 806 participants (531 females, 253 males, and 22 identifying as trans/intersex, or other) with a combined M age of 16.06 years, and a range of mental health issues and conditions including anorexia nervosa, obesity, emotional and general mental health concerns. Results: App functionality included monitoring, assessment, psychoeducation and skills practice. Apps were used independent of ongoing practitioner support in all studies. Apps were used for intake, assessment and intervention. Overall, app use was reported as beneficial. Discussion: Function-based categorisation of apps permits practitioners to consider and select apps that 'fit' best with individualised, evidence-based practice approaches. Limitations of independent use are identified and discussed, and recommendations for adjunctive use (i.e. alongside ongoing practitioner support) are presented. Clinical recommendations and suggestions for future research are provided.